Effect of Environmental Factors on Grassland Biodiversity and Biomass in the Zhangye Region - Yazhou Liu; Meiling Zhang; Youyi Zhao; Jianzhou Wei; Shengwei Zhou; Xiaoyan Shi (Agronomy)
Grassland ecosystems, which are essential for biodiversity and ecosystem services, are increasingly vulnerable to degradation, primarily driven by climate change and soil variability. Understanding the influence of environmental factors on these indicators is critical for addressing grassland degradation and promoting sustainable land management practices. This study investigates the influence of environmental factors, particularly temperature, precipitation, and soil properties, on species diversity and biomass in the arid and semi-arid grasslands of the Zhangye region, China. Field sampling was performed at 63 sites to collect data on vegetation characteristics, biomass, and soil properties, complemented by climate data. This study investigates the mechanisms through which abiotic factors influence biomass and species diversity. The results indicate that soil moisture and relative humidity, as related factors, are significantly positively correlated with both species diversity and biomass, thereby highlighting the stress induced by temperature in arid ecosystems. Furthermore, soil bulk density and pH were identified as critical mediating factors that influence biomass indirectly through their impact on soil moisture. These findings underscore the complex role of climate–soil interactions in shaping grassland ecosystems and offer essential insights for developing adaptive strategies to manage and mitigate grassland degradation in response to climate change.